AI Among Us: What Should We Do? - Pérez, Diana Inés (Resonancias. Revista de Filosofía, 2024)
In this work I focus on the ways in which human beings interact with AI systems currently existing in our societies. I show that certain types of forms of interaction are the basis for considering such systems as “intelligent” given the very origin of the development of AI based on the “Turing Test”. I distinguish two types of developments and their effects, taking as criteria the forms of interaction that these systems demand. Finally, I highlight some of the challenges we face today, the central role that the humanities and social sciences will have in this area, and I suggest some possible lines of action.